Análise da sustentabilidade do ciclo de vida do nanoferro na remediação de áreas contaminadas - Visentin, Caroline (2023)
Sustainability has become a key factor in recent decades. Numerous methods have been developed to assess sustainability, such as the Life Cycle Sustainability Assessment (ASCV). Meanwhile, the use of nanomaterials in remediation has been growing over the years, and nanoiron (nFeZ) is the most used. Therefore, the objective of this work is to evaluate the sustainability of the life cycle of nanoiron in the remediation of contaminated areas. To achieve the objective, the scope of the research was divided into four main stages: (1) assessment of the sustainability of the nFeZ production life cycle, with nine nFeZ production methods being evaluated; (2) the assessment of the sustainability of the life cycle of the application of nFeZ in the remediation of contaminated areas, through the analysis of five worldwide case studies in different configurations; (3) feasibility analysis of using nFeZ in the remediation of contaminated areas in Brazil, comparing with the traditional remediation techniques most used in the country; These three steps involve the application of Life Cycle Assessment (LCA), Life Cycle Costing (CCV), Social Life Cycle Assessment (ACV-Social) and Life Cycle Sustainability Assessment (ASCV; (4) and finally, a method of aggregating the results of the ASCV life cycle analyzes was developed, through a composite sustainability index. The final method was defined based on an analysis of different methods used in aggregating the results of life cycle analyzes and also considering the participation of researchers in the area to determine the importance of different selection criteria for these aggregation methods. Thus, the proposed method consists of optimizing aggregation methods, considering a sustainability score and rating scale. In general, it is possible to highlight that the results obtained give consistency to the study and indicate its relevance. This study fills important scientific gaps in all its stages, contributing to the state of the art in the area of ​​sustainable remediation, nFeZ and ASCV. It is concluded that the use of nFeZ in remediation may not be sustainable, and considering the Brazilian perspective, important configurations are necessary. Furthermore, the proposed ASCV method provides a consistent analysis, overcoming the limitations of existing aggregation methods and facilitating and contributing to the sustainability analysis process.